Evaluation of the Integrated Plastic and Reconstructive Surgery Prerequisite Core Surgical Training Experience: A Residents' Perspective. Issue 4 (October 2018) - Pfaff, Miles J.; Morrison, Shane D.; Rezzadeh, Kameron; Januszyk, Michael; Delong, Michael R.; Lee, Justine C.; Rudkin, George
Abstract : Background: A key educational component of the integrated plastic and reconstructive surgery (PRS) training model is the prerequisite, or core, experiences. The aim of this study is to assess the integrated PRS residents' experience with this early part of training. Methods: A 20-question survey was developed and piloted before deployment to integrated PRS training programs from 4 United States Census regions. Respondents were asked to characterize their prerequisite clinical and operative experiences. Results were analyzed using pairwise correlation statistics and logistic regression modeling following Bonferroni correction for multiple hypothesis testing. Results: One hundred ninety six residents (22 programs) participated in the study (response rate, 65.3%). The majority of residents were satisfied with their prerequisite experiences. Most did not take the American Board of Surgery In-Training Examination, which was perceived as noncontributory to PRS training. The majority of residents preferred to have fewer prerequisite experiences. Operative hours per week were predictive of resident satisfaction with the clinical and operative prerequisite experiences (both P < 0.001). Perception of general surgery program director investment in PRS education was also predictive of resident satisfaction with clinical and operative experiences ( P = 0.05 and P < 0.001, respectively). Conclusions: The present study demonstrates that PRS residents are satisfied with the quality of prerequisite training but prefer less overall. Reevaluation of the benefits of the American Board of Surgery In-Training Examination and individual essential rotations for resident education would be welcomed. Furthermore, this study identifies the residents' clinical and operative experience and perceived general surgery program director involvement as important determinants of integrated resident satisfaction with prerequisite training. Abstract : Supplemental digital content is available in the text.